Barbara L. Wilson letter to Thomas H. Kent regarding bird sightings, December 1, 1979. - Wilson, Barbara L.et al (1979)
Field notes contributed by Barbara L. Wilson in a letter to Thomas H. Kent, December 1, 1979. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1979. Epson - sheet feed/flatbed